Towards FAIR: first measurements of metallic magnetic calorimeters for high-resolution x-ray spectroscopy at GSI - Hengstler, Daniel; Keller, Michael; Schötz, Christian Dominik; Geist, Jeschua; Krantz, Matthäus; Kempf, Sebastian; Gastaldo, Loredana; Fleischmann, Andreas; Gassner, T.; Weber, G.; Märtin, R.; Stöhlker, Th; et al. (Physica scripta, 2015)
Metallic magnetic calorimeters are energy dispersive particle detectors that are operated at temperatures below . Applied to x-ray spectroscopy they combine the high energy resolution of crystal spectrometers with the large energy bandwidth of semiconductor detectors. After the absorption of a photon its energy is converted into heat. A paramagnetic alloy converts the temperature change into a change of magnetization that is read out by a sensitive superconducting quantum interference device magnetometer. With such a metallic magnetic calorimeter we performed two successful measurements at the internal gas target of the experimental storage ring at GSI. In the first beamtime lithium-like Au-ions were targeted on a N2 and a Xe gas target, respectively. In the second beamtime we observed a projectile beam of bare Xe ions interacting with a Xe gas target. In both experiments we achieved an energy resolution below from to . We were able to detect K-lines of Xe ions of different charge states, including the Lyman series up to Ly-η and could resolve the Ly-β-doublet in H-like Xe.